2004
DOI: 10.1158/1078-0432.ccr-03-0640
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C-Met Oncogene as a Broadly Expressed Tumor-Associated Antigen Recognized by Cytotoxic T-Lymphocytes

Abstract: Conclusion: Our results demonstrate that c-Met oncogene is a novel tumor rejection antigen recognized by CTL and expressed on a broad variety of epithelial and hematopoietic malignant cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
1
26
1
Order By: Relevance
“…In addition to CA-IX, ADFP, Cyclin D1, C-MET, and RGS-5 are also overexpressed in ccRCC (14). In contrast to published reports (33,34), we found that ADFP expressed more frequently (65%) than C-MET (30%). Cyclin D1 is a cell-cycle regulator crucial for the G 1 -S transition (35) and is overexpressed in many cancers including colorectal and breast carcinoma (36,37).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In addition to CA-IX, ADFP, Cyclin D1, C-MET, and RGS-5 are also overexpressed in ccRCC (14). In contrast to published reports (33,34), we found that ADFP expressed more frequently (65%) than C-MET (30%). Cyclin D1 is a cell-cycle regulator crucial for the G 1 -S transition (35) and is overexpressed in many cancers including colorectal and breast carcinoma (36,37).…”
Section: Discussioncontrasting
confidence: 96%
“…ADFP, C-MET, and RSG-5 are not immunogenic in patients with ccRCC, as we did not detect T-cell responses specific for these antigens, despite their frequent overexpression. This finding is in agreement with previously published data on rare T-cell responses in patients with ccRCC (15), even though ADFP-and C-MET-specific T cells could be expanded from the blood of healthy donors (33,34). RGS-5 overexpression did not result in detectable RGS-5-specific T-cell responses in our cohort, although such responses were reported in the blood of healthy donors and patients with acute myeloid leukemia (42).…”
Section: Discussionsupporting
confidence: 93%
“…PCR products were sequenced to confirm correct amplification. Control primers for glyceraldehyde-3-phosphate dehydrogenase are TCA AGG TCG AGT CAA CGG ATT TGG T and CAT GTG GGC ATG AGG TCC ACC AC, amplifying 983 bp, as described (Clontech), and control primers for ␤2-microglobulin are GGG TTT CAT CCA TCC GAC AT and GAT GCT GCT TAC ATG TCT CGA, amplifying 224 bp, as described (32).…”
Section: Methodsmentioning
confidence: 99%
“…A volume of 1.0 ml of cDNA was subjected to PCR (32 cycles) as described earlier. 21,22 The integrity of the RNA and the efficiency of the cDNA synthesis were checked by amplifying the b2-microglobulin gene with an intron-spanning primer pair. Primer sequences were deduced from published cDNA sequences: ERK2 5 0 -ccacc catatctggagcagt-3 0 and 5 0 -cagtcctctgagcccttgtc-3 0 , IRAK1 5 0 -gacc ctgtctctgccaaaaa-3 0 and 5 0 -caggctggagtgcagtcata-3 0 and MyD88 5 0 -gcacatgggcacatacagac-3 0 and 5 0 -gacatggttaggctccctca-3 0 .…”
Section: Reverse Transcription-pcrmentioning
confidence: 99%
“…Remaining sequences were published elsewhere. 21,22 The semiquantitative estimation of target gene expression was carried out by normalization of the density volumes of ethidium bromidestained PCR products to the corresponding b2-microglobulin-PCR products (target gene-PCR product [S {pixel, gray values}]/ b2-microglobulin [S {pixel, gray values}]) using a CCD camera and gel analysis system (BioDocAnalyze video, Whatman Biometra, Gö ttingen, Germany). 23 Values were expressed as percentage of the 24 h value with IL-4 and GM-CSF (100%).…”
Section: Reverse Transcription-pcrmentioning
confidence: 99%